Perspectives, Changes and Resignification of the Teaching of History in the Honduras of the Bicentennial - Guevara Pineda, Erick José (2021)
The new social dynamics have caused a significant turn in the teaching of the social sciences and particularly in history. The purpose of this article is to present a non-experimental descriptive case study; developed at the Choluteca associated center of the Metropolitan University of Honduras -located in the municipality of Choluteca- and the Villa Marco Official Institute -located in the municipality of Marcovia- in the southern region of Honduras. Which have allowed the marking of elements to be deconstructed for the understanding of the processes that as bicentennial societies we must consolidate or re-signify. This work deals with the need to merge the history taught by the researched, coupling a new vision of how to approach the curricular contents, the strengthening of decision-making by students and some considerations that as teachers in virtual or blended interaction we must assert itself in the Honduras of the XXI century; such as the proper dosage of the contents, the management of platforms or virtual classrooms, as well as games in real time that allow the idea of constant interaction and the monitoring of the students who deserve it with the greatest need.